Crop and Weed Management Practices of Snap Bean (Phaseolus vulgaris) Production Fields in the United States - Pavle Pavlovic; Jed B. Colquhoun; Nicholas E. Korres; Rui Liu; Carolyn J. Lowry; Ed Peachey; Barbara Scott; Lynn M. Sosnoskie; Mark J. VanGessel; Martin M. Williams II (HortScience)
Agronomic and weed management practices employed by growers in the production of snap bean (Phaseolus vulgaris) for the processing industry are poorly characterized. To address this knowledge gap, records of agronomic and weed management practices from 358 snap bean fields were obtained from collaborating processors. These fields encompassed three production regions in the United States: the Northwest (NW), Midwest (MW), and Northeast (NE). The obtained records were formatted to be more suitable for presentation or analysis. Forty cultivars were used across all three regions, primarily of green round podded type (∼90% of all fields). However, it was common for only relatively few cultivars to be widespread in each region. Seeding rates were substantially higher (by more than 100,000 plants/ha on average) in the NW region. Crop row widths were also narrower in the NW region compared with other regions. Planting and harvest occurred across a wide range of dates in all three production regions, with the NW having a delay of ∼10 days. The most common crop in rotation with snap bean was usually some type of corn, although the NW region had more variability in crop rotation. Spring tillage and irrigation were commonly used practices across all regions. Weed management was dominated by the use of interrow cultivation and a narrow spectrum of preemergence and postemergence herbicides. However, interrow cultivation was not used as much in the NW compared with the other two regions. Snap bean grown in the NW production region showed a departure in agronomic and weed management practices compared with the MW and NE production regions.